Physico-chemical properties of evaporated epa (40÷56% ) from phosphorites of the central Kyzylkum (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article presents a technology for producing high-quality phosphorus fertilizers by increasing the concentration of extraction phosphoric acid (EPA) obtained from low-grade phosphorites of the Central Kyzylkum Desert. Since impurities from phosphorite ore pass into the EPA and exceed permissible levels in the final product, purification and concentration of the acid are required. A two-stage evaporation method was used to obtain EPA with 25.13–27.5% P₂O₅. Four EPA samples and sixteen subsamples were analyzed to track changes in composition during concentration. Removing a magnesium-rich precipitate (40–46% P₂O₅) improves processability. Concentrated acids (45–55% P₂O₅) enable the production of high-quality mineral fertilizers.
Keywords: Phosphorus, phosphorite, extraction phosphoric acid, concentration, purification, filtration, fertilizers, acid properties